Improvement Of Power Quality Using Shunt Active Power Filter In An Electrical Distribution System Using Eerl-Smc - Vinay Kumar Naguboina; Satish Kumar Gudey (Universitas Nurul Jadid, 2021)
In this paper a three phase Shunt Active Power Filter (ShAPF) is proposed to address the current related issues in a three phase Electrical Distribution System (EDS). A sliding mode controller (SMC) and an Enhanced Exponential Reaching Law based SMC (EERL-SMC) is proposed for a ShAPF to compensate the load current. The controller’s performance is tested by injecting the current harmonics into the system. A non-linear load along with different loads on the distribution side is connected in parallel in a distribution network at Point of common coupling (PCC). Modelling of the system is done using state space analysis. Stability of the system is analyzed using the state feedback approach. The reference source currents are generated using instantaneous PQ theory. For variations in the load, the THD in the source current is realized. It is found that EERL-SMC is more effective for a ShAPF in reducing the high frequency oscillations and settling time for convergence. The source voltage and current waveforms are observed to be sinusoidal in nature. Both the controllers are effective in reducing the THD levels in the source current as per the IEEE standards. A comparison between the controllers is presented in terms of settling time, THD in source current. PSCAD v4.6 is used for simulation works.